Natural rights theories. Their origin and development. - Tuck, Richard (Cambridge University Press, 1981)
This book shows how political argument in terms of rights and natural rights began in medieval Europe, and how the theory of natural rights was developed in the seventeenth century after a period of neglect in the Renaissance. Dr Tuck provides a new understanding of the importance of Jean Gerson in the formation of the theories, and of Hugo Grotius in their development; he also restores the Englishman John Selden's ideas to the prominence they once enjoyed, and shows how Thomas Hobbes's political theory can best be understood against this background. In general, the book enables us to understand more fully the characteristics of the natural rights theories available to the men of the Enlightenment, and thereby to appreciate the complexity and equivocal nature of modern right theories.